2013
DOI: 10.1590/s0004-27302013000300004
|View full text |Cite
|
Sign up to set email alerts
|

Hipotireoidismo congênito: recomendações do Departamento de Tireoide da Sociedade Brasileira de Endocrinologia e Metabologia

Abstract: Congenital hypothyroidism (CH) is the most common congenital endocrine disorder, with an incidence of 1:2,000 to 1:4,000 live births and it is a leading preventable mental retardation. Neonatal Screening Programs allow early identification of the disease and the adequate treatment of affected children can avoid the complications related to deprivation of the hormone. Most cases of primary congenital hypothyroidism (85%) are due to thyroid dysgenesis (ectopia, hypoplasia or agenesis) while the remaining result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 47 publications
1
20
0
9
Order By: Relevance
“…Currently, CH has a worldwide incidence of 1 in approximately 3,500 live births 4 . A similar incidence has been observed in Brazil, where the estimated rates range from 1:2,595 to 1:4,795 live births 1,18 . In the PNTN, CH is screened by dosing thyroid-stimulating hormone (TSH) with filter paper.…”
Section: Discussionsupporting
confidence: 76%
“…Currently, CH has a worldwide incidence of 1 in approximately 3,500 live births 4 . A similar incidence has been observed in Brazil, where the estimated rates range from 1:2,595 to 1:4,795 live births 1,18 . In the PNTN, CH is screened by dosing thyroid-stimulating hormone (TSH) with filter paper.…”
Section: Discussionsupporting
confidence: 76%
“…The cutoff of confirmatory serum TSH of 10 µU/mL would imply a loss of 70 cases of permanent conditions (23 CH and 47 hyperthyrotropinemia). We also found that 15.2% of the children with serum TSH levels between 4.2 and 6 µU/mL would not have been diagnosed if the TSH cutoff point was 6 µU/mL, according to the national recommendation (22).…”
Section: Discussionmentioning
confidence: 73%
“…Early diagnosis and treatment of children with CH bring enormous benefits to the family and community, as they avoid social, emotional and financial costs through prevention of intellectual disability (4) . However, although early screening programs for CH have proven effective in reducing intellectual disability, the key issue is identifying neurocognitive sequelae, even the subtlest ones, which may persist despite early treatment (2,(4)(5)(6)9,11,19) . Studies have reported that individuals with CH may present attention, memory, visuocognitive, visuospatial and psychomotor disorders (1,10,12,14,(18)(19)(20)24) .…”
Section: Discussionmentioning
confidence: 99%
“…Congenital hypothyroidism (CH) is a pediatric endocrine disorder characterized by insufficient thyroid hormone production caused by thyroid dysgenesis or dysormonogenesis (1)(2)(3) . Its incidence is of approximately 1 in 3000-4000 newborns, with a two to three-fold higher prevalence in females (4)(5)(6) . It is the leading cause of preventable intellectual disability when diagnosed and treated early (4,(7)(8)(9)(10)(11) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation